2015
DOI: 10.1161/strokeaha.115.010614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Age With Stroke and Death in Anticoagulated Patients With Nonvalvular Atrial Fibrillation

Abstract: Background and Purpose-The prevalence of atrial fibrillation increases with age, but age-specific data on the incidence of stroke and death in anticoagulated patients with atrial fibrillation are more limited, particularly with regard to comparisons of relative risks of clinical outcomes between the different age strata in relation to quality of anticoagulation control among warfarin users. Methods-We investigated the incidence of adverse outcomes between tertiles of age groups (age, <67 [n=722]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…European Stroke Organisation (ESO) guidelines do not specifically contraindicate the use of OACs in patients with dementia, but do not recommend their use in patients with comorbid conditions such as falls or poor compliance . However, studies that investigated the use of warfarin for prevention of thromboembolism in AF in different age groups have shown a higher rate of bleeding in the older population, but also a higher rate of IS which would indicate a greater need for anticoagulation (Table ) . However, older patients (>75/80 years) in these studies are significantly under‐represented.…”
Section: Management Of Acute Ischaemic Strokementioning
confidence: 95%
“…European Stroke Organisation (ESO) guidelines do not specifically contraindicate the use of OACs in patients with dementia, but do not recommend their use in patients with comorbid conditions such as falls or poor compliance . However, studies that investigated the use of warfarin for prevention of thromboembolism in AF in different age groups have shown a higher rate of bleeding in the older population, but also a higher rate of IS which would indicate a greater need for anticoagulation (Table ) . However, older patients (>75/80 years) in these studies are significantly under‐represented.…”
Section: Management Of Acute Ischaemic Strokementioning
confidence: 95%
“…A generally accepted quality measure in warfarin therapy is the time patients spend within the therapeutic range (percent time in therapeutic range; TTR)[ 3 , 4 ]. An inverse correlation between TTR and hemorrhagic and thromboembolic complications has been established and it has been suggested that the benefits of warfarin therapy may be outweighed if the quality of warfarin therapy is too poor[ 5 8 ]. In continuation hereof, it may be beneficial to increase TTR, if possible, as it would decrease the risk of therapy-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the present community-based study, OAC therapy was still underused (<60%) in both Japanese and British elderly populations. The risks are probably multifactorial, perhaps reflecting a perception that elderly patients with AF carry a relatively higher risk of major bleeding, but the relative benefits/harms of OAC for stroke or mortality and major bleeding showed consistency despite increasing age strata in a real-world and clinical trial setting 12 13…”
Section: Discussionmentioning
confidence: 99%